Mental Workload Evaluation for PMM Outbound Student in X University (Unix) Using NASA-TLX Method - Isnaini, Wildanul; Khoiri, Halwa Annisa; Cahyaningtyas, Putri (Spektrum Industri, 2022)
Program Mahasiswa Merdeka (PMM) is one of the MBKM program. This program allows student to study in different university and majors. It was attended by students of Engineering Faculty from UNIX in State and Private University throughout Indonesia. By participating PMM, the student have overload credits because they have to finish double credit from homebased and destination university. This condition affects the burden on students both physically and mentally. This mental burden of students has an impact on student achievement academically, so the mental burden analysis is needed. In this study, an evaluation of the mental workload was carried out using the NASA-TLX approach. The result found that in general 75% of students experienced a very high workload. The percentage of students who take PMM in State University as much as 50% is in the category of high mental workload and 50% is very high category. The percentage of students who take PMM in Private University is 25% in the very high category and 75% is in the high category. From this study, UNIX can have some consideration about providing the brief (tips and tricks) before PMM for student mental preparation and choosing the Private University for destination university.